2008
DOI: 10.1073/pnas.0712044105
|View full text |Cite
|
Sign up to set email alerts
|

IKKα is a critical coregulator of a Smad4-independent TGFβ-Smad2/3 signaling pathway that controls keratinocyte differentiation

Abstract: Cell-cycle exit and differentiation of suprabasal epidermal keratinocytes require nuclear IB kinase ␣ (IKK␣), but not its protein kinase activity. IKK␣ also is a suppressor of squamous cell carcinoma (SCC), but its mode of action remains elusive. Postulating that IKK␣ may serve as a transcriptional regulator in keratinocytes, we searched for cell-cycle-related genes that could illuminate this function. IKK␣ was found to control several Myc antagonists, including Mad1, Mad2, and Ovol1, through the association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
159
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 41 publications
11
159
0
1
Order By: Relevance
“…15 Also, it has been reported that IKKa regulates the expression of Max dimer protein 1 (Mad1) and ovo-like 1 (Ovol1), which are differentiation inducers and c-Myc antagonists. 20 Thus, we evaluated whether different levels of transgenic IKKa have different effects on EGFR activity, and on Mad1 and Ovol1 expression levels. Western blotting showed that Tg-7-IKKa and Tg-4-IKKa not only repressed EGFR activity in the skins of mice with a WT background, but also strongly repressed IKKa loss-induced EGFR activity in the skin of Ikka À/À mice in an IKKa dose-dependent manner (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…15 Also, it has been reported that IKKa regulates the expression of Max dimer protein 1 (Mad1) and ovo-like 1 (Ovol1), which are differentiation inducers and c-Myc antagonists. 20 Thus, we evaluated whether different levels of transgenic IKKa have different effects on EGFR activity, and on Mad1 and Ovol1 expression levels. Western blotting showed that Tg-7-IKKa and Tg-4-IKKa not only repressed EGFR activity in the skins of mice with a WT background, but also strongly repressed IKKa loss-induced EGFR activity in the skin of Ikka À/À mice in an IKKa dose-dependent manner (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, IKKa doses are also important for suppressing excessive mitosis of keratinocytes. On the other hand, Descargues et al 20 and Marinari et al 19 have shown that IKKa regulates the expression of Mad1 and Ovol1, c-Myc antagonists, through transforming growth factor-b/smad, in keratinocytes, skin, and skin tumors in human and mice, and that Mad1 and Ovol1 are required to induce keratinocyte differentiation and inhibit keratinocyte proliferation. In the present study, we found that transgenic IKKa substantially induced the expression of Mad1 and Ovol1 in a dose-dependent manner, and that the expression levels of Mad1 and Ovol1 were well correlated with IKKa levels and differentiation levels in the skin and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations